China 2025 - Richmond, Simon (Lonely Planet guidebooks., 2025)
Lonely Planet's China is our most comprehensive guide that extensively covers all the country has to offer, with recommendations for both popular and lesser-known experiences. Climb the Great Wall, wander the Forbidden City and visit historic Tiananmen Square; all with your trusted travel companion.